Herbicide Program Alternatives for Managing Weeds in Double-crop Soybean Scenarios in Northeast Kansas - Joaquin L. Enrria; J. Anita Dille (Kansas Agricultural Experiment Station Research Reports, 2025)
Managing economically problematic weeds in double-crop soybean systems is often challenging for producers in northeastern Kansas. This study aims to evaluate weed control and the economics of herbicide programs in various scenarios. The first experiment compared regular and premium herbicide programs at PRE and POST application timings. Premium soil-residual and foliar herbicide programs had greater weed control after both PRE and POST application timings, but did not lead to a higher gross margin. The second experiment consisted of four herbicide programs applied at POST timing at the V4 soybean growth stage. Increasing the herbicide rate in late applications did not improve overall weed control. In general, two-pass programs had better weed control than one-pass programs for late applications.
Keywords: economics; herbicide application timing; weed control